DOI: 10.14264/uql.2015.516
|View full text |Cite
|
Sign up to set email alerts
|

Life-cycle perspectives for urban water systems planning

Abstract: Urban water systems around the world are going through a period of substantial change: they are evolving towards more complex water supply alternatives; are being placed under increasing pressure to achieve higher quality effluent and biosolids discharges; and are being confronted with a growing number of broader environmental management challenges. This thesis explored the use of the Life Cycle Assessment (LCA) methodology for assisting in that process of change, because of LCA's strengths in combining practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 108 publications
(250 reference statements)
0
2
0
Order By: Relevance
“…First, by using the maximum values allowed by the legislation we are probably overestimating these impacts. Second, the limitations of current toxicity models for assessment of metals are being discussed in literature (Hospido et al, 2005;Corominas et al, 2013b;Lane, 2015) and studies have confirmed wide variability of the toxicity impacts depending on the method used (e.g. (Gandhi et al, 2011) and have reported large uncertainties (Niero et al, 2014).…”
Section: Integrated Assessment Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, by using the maximum values allowed by the legislation we are probably overestimating these impacts. Second, the limitations of current toxicity models for assessment of metals are being discussed in literature (Hospido et al, 2005;Corominas et al, 2013b;Lane, 2015) and studies have confirmed wide variability of the toxicity impacts depending on the method used (e.g. (Gandhi et al, 2011) and have reported large uncertainties (Niero et al, 2014).…”
Section: Integrated Assessment Discussionmentioning
confidence: 99%
“…(Gandhi et al, 2011) and have reported large uncertainties (Niero et al, 2014). Lane (2015) argues that LCA Terrestrial Ecotoxicity models contradict the best available Australian risk assessment, and should be excluded from analysis of biosolids disposal options. In fact, application of biosolids to agriculture is a common practice in Spain which is also promoted by the government with the objective to achieve 70% of biosolids application to agriculture in 2015 (BOE núm.…”
Section: Integrated Assessment Discussionmentioning
confidence: 99%